Lost in translation: translational interference from a recurrent mutation in exon 1 of MECP2 - Saxena, A; de Lagarde, D; Leonard, H; Williamson, S L; Vasudevan, V; Christodoulou, J; Thompson, E; MacLeod, P; Ravine, D (Journal of medical genetics, 2006)
Background: Rett syndrome (RTT) is an X linked neuro-developmental disorder affecting mostly girls. Mutations in the coding region of MECP2 are found in 80% of classic RTT patients. Until recently, the region encoding MECP2 was believed to comprise exons 2, 3, and 4 with the ATG start site located at the end of exon 2 (MeCP2_e2). Methods: Recent reports of another mRNA transcript transcribed from exon 1 (MeCP2_e1) prompted us to screen exon 1 among RNA samples from 20 females with classic or atypical RTT. Results: A previously reported 11 base pair deletion in exon 1 was detected in one subject with a milder phenotype. Although RNA expression for both protein isoforms was detected from the mutant allele, evaluation of MeCP2 protein in uncultured patient lymphocytes by immunocytochemistry revealed that MeCP2 protein production was restricted to only 74–76% of lymphocytes. X chromosome inactivation studies of genomic DNA revealed similar XCI ratios at the HUMARA locus (73:27 with HpaII and 74:26 with McrBC). We have demonstrated that translation but not transcription of the MeCP2_e2 isoform is ablated by the 11 nucleotide deletion, 103 nucleotides upstream of the e2 translation start site. Conclusions: These findings reveal that nucleotides within the deleted sequence in the 5′-UTR of the MeCP2_e2 transcript, while not required for transcription, are essential for translation.